Wpływ opodatkowania na przepływy BIZ między krajami UE - Suwalski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The aim of this article is to examine impact of taxation on flows of FDI inside the UE. Special attention was paid to the theory of tax competition. Author also considers differentiation between effective and nominal level of taxation. In article analysis is carried out of correlation between level of taxation and inflow of foreign direct investments.
Keywords: opodatkowanie dochodów kapitałowych; bezpośrednie inwestycje zagraniczne; Unia Europejska; stawka podatkowa